Caracterização sedimentar de fundo do baixo curso do rio araguari, Estado do Amapá, entre o igarapé santana e a área próxima a foz - SOUZA, Jefferson Robson araújo de (2019)
The estuary of the Araguari river is a system dominated by tides that reach about 5 feet tall in its mouth, and that enter the estuary following their meandering segments, constituting the most significant drainage system of the state of Amapá in length, width and volume of water, considering its lower course restricted to the south by the Amazon river and to the north by the Lakes Region of Amapá. For the characterization of bottom’s sedimentation of the lower course Araguari river were analyzed sub-samples of sediments collected during the second expedition performed by the staff of the Instituto de Pesquisas Científicas e Tecnológicas do Estado do Amapá – IEPA to the Biological Reserve of Piratuba Lake in November 2005 . In the 17 profiles drawn in lines across the river course with equidistance of 5 km were collected, through a sampler of Petersen, 70 sediment samples weighing approximately 1 kg, after which the work done in the laboratory could be inferred that from the classification by the average of the grains size the area presents its sedimentary constitution represented basically by pelitic sediments and that according to the classification of sediment analysis from Folk & Ward, were obtained three textural subclasses that are represented by medium silt, fine silt and coarse clay. These results were essential for making the letter distribution of sediments of the Araguari river, on the stretch between the Santana creek and the proximal area to its mouth.